Pengaruh Sistem Informasi Akuntansi Penjualan Kredit Terhadap Pengendalian Internal Penjualan Kredit : (Studi pada salah satu perusahaan distributor kesehatan di Jawa Barat) - Nenden Adiya Yassin; Boy Suzanto; Haris Nurdiansyah; Jimmy Rusjiana (Acman: Accounting and Management Journal, 2021)
The utilization of information technology in expediting the information process is beneficial for companies in the efficiency of their production processes. For this reason, companies need to improve efficiency concerning financial information so that the use of information technology can carry out effectively. This study departs from the problems that occur in the object of research, which indicate a gap in credit sales internal control. This study aims to determine the effect of credit sales information systems on credit sales internal control. The research method used is verification with a simple regression analysis technique. The results showed a significant effect of credit sales information systems on credit sales internal control. The study results recommend that interested parties, in this case, the company pay more attention to the internal control of credit sales to reduce the possibility of errors that occur in the field.